Bacterial Menigitis and Deafness - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
Dexamethasone (.15 mg/kg/bwt q 6 hr for 4 days) was considered beneficial in the treatment of infants and children with bacterial meningitis, particularly in preventing deafness, in two double blind, placebo-controlled trials involving 200 patients treated in the Dept of Pediatrics, University of Texas at Southwestern Medical Center, Dallas, TX.